2011
DOI: 10.1001/jama.2011.1052
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of War-Related Mental Health Conditions and Association With Displacement Status in Postwar Jaffna District, Sri Lanka

Abstract: Among residents of Jaffna District in Sri Lanka, prevalence of symptoms of war-related mental health conditions was substantial and significantly associated with displacement status and underlying trauma exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
128
7
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(145 citation statements)
references
References 17 publications
5
128
7
5
Order By: Relevance
“…Though prevalence of depression is higher among inward TB patients than the general population of Colombo, it was comparable to the prevalence of depression among internally displaced persons in post-war Jaffna district and among pre dialysis CKD patients [2,3]. But among TB patients, prevalence of anxiety was lower than internally displaced Jaffna population (32.6%) and depression was lower than patients with MI [5,8]. A study done in Pakistan using similar scales had shown that 46% depression and 47% anxiety among patients with TB [6].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Though prevalence of depression is higher among inward TB patients than the general population of Colombo, it was comparable to the prevalence of depression among internally displaced persons in post-war Jaffna district and among pre dialysis CKD patients [2,3]. But among TB patients, prevalence of anxiety was lower than internally displaced Jaffna population (32.6%) and depression was lower than patients with MI [5,8]. A study done in Pakistan using similar scales had shown that 46% depression and 47% anxiety among patients with TB [6].…”
Section: Discussionmentioning
confidence: 71%
“…Also, prevalence of depression was 22.2% and anxiety was 32.6% among internally displaced persons in post-war Jaffna District [5]. Studies have shown an association between TB and common mental disorders (46.3%-80%) [6].…”
Section: Introductionmentioning
confidence: 94%
“…Questionnaire was translated into Tamil and back-translated into English by different translators to ensure accuracy. A formal validation was not carried out (16). The scale has also been translated into Sinhala and used in a study assessing psychological morbidity in snake envenoming (17).…”
Section: Hopkins Symptom Checklist-25 (Hscl-25)mentioning
confidence: 99%
“…This is higher than the 16% depression and 21% PTSD reported 20-21 months after the tsunami in the general population in southern Sri Lanka [10]. A study from Jaffna district in the northern province of Sri Lanka in 2009, shows depression in 42% and PTSD in 13% of displaced civilians [11]. A study done in 1991 in Jaffna district reported 25% major depression, 27% PTSD, 41% somatization and 26% anxiety disorders in a civilian population following war trauma [12].…”
Section: Discussionmentioning
confidence: 90%